Republic of Madagascar : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses key findings of the Ex Post Assessment of Longer-Term Program Engagement for Madagascar. The paper focuses on performance during the programs supported by the 1989 and 1996 Enhanced Structural Adjustment Facility programs, and the 2001 Poverty Reduction and Growth Facility. Despite nearly continuous involvement by the IMF, other international financial institutions, and bilateral donors, economic progress has been slow. Only the most recent years have witnessed inroads into poverty reduction of some significance. However, the country's growth base remains narrow, and its institutional framework and governance weak.